Research on the Changing Law of Tunnel Temperature Field and the Application of Air Curtain System in Cold Regions - Renyuan Wang; Yongquan Zhu; Yan Gao; Zhichun Fang; Chaoyi Ma (Advances in Materials Science and Engineering)
In this study, a tunnel temperature field model test bed is built according to the similarity principle to study the variation law of temperature in the tunnel in the cold season. According to the variation law of temperature in the tunnel, a new active thermal insulation measure, namely, an air curtain system, is developed. According to the principle of flow function superposition and heat balance, the governing equation of air curtain system is obtained. Taking the Zhengpantai tunnel as an example, the feasibility of the air curtain system is verified, and the jet angle of air curtain is optimized. The research results show that outside temperature and surrounding rock temperature are the main factors affecting the temperature field of tunnels in cold regions. The calculation results show that the air curtain system can effectively prevent tunnel freezing damage. The optimal jet angle of air curtain system should be 30°–40°. When the outside temperature is extremely low, multiple air curtains can be used in series to heat the temperature in the tunnel, and it is recommended that the distance between the two air curtains is not less than 20 m.